Evembe's Sur la terre en passant and the Poetics of Shame - Richard Bjornson (Studies in 20th & 21st Century Literature, 1980)
In Sur ta terre en passant, Evembe fashions a poetics of shame from the ordinary experiences of life in a large African city (Yaounde). He does it in such a way that the hallucinatory qualities and scabrous details of one individual's state of consciousness mirror the malaise which characterizes the larger social reality. The protagonist Iyoni (whose name means «shame» in the dialect of Evembe's native Kribi) experiences both misery and social respectability in an environment where traditional values have been lost, only to be replaced by artificial, dehumanizing hierarchies and an attitude of materialistic acquisitiveness. Despite the mysterious illness which is eroding his will to live, Iyoni always attempts to maintain a dignified pose, and he seeks to project his own poetic sensitivity and his morality of love and compassion onto the larger social fabric, but his physical body proves incapable of sustaining his ideals, and when he regards himself as a machine which ingests food and ejects clots of blood and excrement, he has begun to lose confidence in himself as a loving, feeling person capable of working toward a more noble social order. The resultant anxiety and shame permeate Evembe's novel, which has been undeservedly neglected due to its implicit antiestablishment critique of church, state, and the Negritude movement.
Keywords: Evembe; Sur la terre en passant; poetics of shame; shame; hallucinations; consciousness; reality; social realty; materialism; hierarchy; antiestablishment; critique of church; critique of state; critique of the Negritude movement; Negritude movement; state; church